Utilization Application Mobile for Speed Up Searching Boarding House Android Based - Guntur, Surya; Manurung, Asrar Aspia; Hasibuan, Ahmad Riady (Ilmu Bersama Center, 2024)
Purwokerto is a city in Central Java Province. Purwokerto's development is currently relatively rapid, both in the economic and educational fields. There are many boarding houses for rent in the Purwokerto area, especially around campuses and business areas. However, the majority of boarding house owners still market their boarding places manually, such as putting up the words 'Accept Boarding House' in front of the house or by hiring a jockey. Along with current technological developments, especially in the smartphone sector, many applications have emerged that help users. To bridge the needs of users and boarding house providers, an application is needed that can display information on boarding houses in Purwokerto. The application was built on a mobile basis with the Android operating system for users who want to find a boarding house. Meanwhile, boarding house providers use a web-based system that can update boarding house advertisements. The method used in preparing this research uses the Waterfall model. The testing stage is carried out by conducting product tests. Product testing is carried out by testing the application using the reliability and attributes durability, conformance, serviceability, apperarance and perceived quality. The Android-based boarding house information system in Purwokerto can help users or boarding house seekers to obtain information about boarding houses more quickly, so the user becomes more efficient in Look for the accommodation you want.